Russian Political Kant after Liberalism: Sergey Hessen on 1924 Kant Jubilee - Modest Kolerov (Кантовский сборник)
Using the Kant jubilee in 1924 as a pretext, Sergey Hessen, a Russian émigré neoKantian, draws no direct political conclusions but sets forth a view of the great philosopher’s legacy from the position of a “legal socialist”, selecting from his heritage those parts of German socialist doctrines that to his mind experienced a departure from a recent flowering of Kantian ideas in NeoKantianism and the collapse of traditional liberalism in the wake of the First World War. The fact that the text was first published in the Berlinbased Russian liberal newspaper “Rul’”, gives us reason to see it not just as a formal jubilee tribute, but as an act addressed to the qualified liberal audience which witnessed thecollapse of liberalism in Russia.